Selection of reference foods for a scale of standards for use in assessing the transitional process from milk to solid food in infants and pre-school children - Sakashita, R; Inoue, N; Tatsuki, T (European Journal of Clinical Nutrition, 2003)
Objective : This paper describes the development of a reliable scale of standards for use in evaluating the progress of the transition from milk to solid food in infants and preschool children. The maturation of chewing and swallowing behavior in infants and young children, which enables processing of solid food, varies, and a scale would assist not only in the instruction of mothers and nurses but also in preventing delay in the introduction of solid food. Design : A range of 159 reference foods were selected on the basis of intake during the period of transition from liquid to solid food. These foods were listed in our previous study, Validity and reliability were tested to create a scale. Methodology : Foods were selected on the basis of 50% of the subjects studied being able to eat them, and on the food groups classified by cluster analyses using the Varclus procedure of SAS. Validity, of the scale was tested by using Pearson's correlation coefficient between the scale score of selected food items and the total score of all 159 food items. The total score of 159 food items was calculated using the general linear models (GLM) procedure of SAS. Reliability was tested using Cronbach's coefficient α. Setting : Public health centers in Aomori, Tokyo, Saitama, Nagano, and Okinawa (Japan). Subjects : Five hundred and eighty healthy mothers and children from 2 to 46 months were randomly selected and 470 (81.0%) completed the study. To avoid regional bias, subjects were drawn from northern to southern prefectures in Japan, namely Aomori, Tokyo, Saitama, Nagano, and Okinawa. Results : Twenty food items were selected. By analyzing the score correlation using Pearson's correlation coefficient ( R =0.97, P <0.001) and GLM ( R 2 =0.95, P <0.001), it was confirmed that these 20 food items adequately represented the original 159. The reliability was also found to be sufficient (Cronbach's coefficient α=0.96). Conclusions : The findings demonstrate that a scale of standards for measuring progress in chewing ability can be created using 20 food items. Such a standard will provide a useful basis against which to assess delay of solid food introduction in childhood. Sponsorship : Grant-in-Aid for Scientific Research, provided by the Japanese Ministry of Education, Science and Culture, Project No. 07838030.